Measurement invariance of the second edition of the Fifteen Factor Personality Questionnaire (15FQ+) over different ethnic groups in South Africa - Holtzkamp, Jani Gerda (Stellenbosch : Stellenbosch University, 2013)
Thesis (MComm)--Stellenbosch University, 2013.